The Colombian National Rice Farmers Organization (Fedearroz) uses CCAFS science and principles to design and implement an agro-climatic service for rice production, reaching 30,000 farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Climate variability affects rice farming. CCAFS scientists developed and deployed a novel forecasting platform in 2017–2018 jointly with farmers organizations, accompanied by novel methods for crop and climate prediction. Based on these, and with the support of the Ministry of Agriculture of Colombia (MADR) and the Food and Agriculture Organization of the United Nations (FAO), Fedearroz developed and deployed a comprehensive climate services platform (http://clima.fedearroz.com.co/index.html). The platform currently provides agro-climatic information to 100 % of the producing areas in Colombia.